2018
DOI: 10.1093/jxb/ery167
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation and phosphorylation: hidden and overt links

Abstract: Post-translational modifications are essential mediators between stimuli from development or the environment and adaptive transcriptional patterns. Recent data allow a first glimpse at how two modifications, phosphorylation and sumoylation, act interdependently to modulate stress responses. In particular, many components of the SUMO conjugation system are phosphoproteins, and some regulators and enzymes of protein phosphorylation can be sumoylated. Equally important, however, a number of proteins can be subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…This phosphorylation allows the recruitment of a specific PIAS SUMO E3 ligase (yet to be described), resulting in SUMOylation of ERK5 (branched SUMO chains) at residues Lys6 and Lys22. Of note, our findings show an interplay between phosphorylation and SUMOylation, as described for other proteins (reviewed in [45]). In this model, covalent SUMO modification of ERK5 would facilitate the dissociation of Hsp90 from the kinase domain (Hsp90 is not dissociated from the ERK5 SUMO-deficient mutant in response to MEK5 activation, Figure 6).…”
Section: Discussionsupporting
confidence: 80%
“…This phosphorylation allows the recruitment of a specific PIAS SUMO E3 ligase (yet to be described), resulting in SUMOylation of ERK5 (branched SUMO chains) at residues Lys6 and Lys22. Of note, our findings show an interplay between phosphorylation and SUMOylation, as described for other proteins (reviewed in [45]). In this model, covalent SUMO modification of ERK5 would facilitate the dissociation of Hsp90 from the kinase domain (Hsp90 is not dissociated from the ERK5 SUMO-deficient mutant in response to MEK5 activation, Figure 6).…”
Section: Discussionsupporting
confidence: 80%
“…This phosphorylation allows the recruitment of a specific PIAS SUMO E3 ligase (yet to be described), resulting in SUMOylation of ERK5 (branched SUMO chains) at residues Lys6 and Lys22. Of note, our findings show an interplay between phosphorylation and SUMOylation, as described for other proteins (reviewed in [45]). In this model, covalent SUMO modification of ERK5 would facilitate the dissociation of Hsp90 from the kinase domain (Hsp90 is not dissociated from ERK5 SUMO-deficient mutant in response to MEK5 activation, Figure 6).…”
Section: Discussionsupporting
confidence: 80%
“…Similar to SUMOylation, there are some proteins which phosphorylation associates with mitochondrial oxidative stress. Accumulating evidence shows that there is an inter-connection between SUMOylation and phosphorylation [118][119][120][121]. Recent studies have shown that obesity and aging decrease SIRT1-mediated SIRT3 deacetylation and reduce SIRT3 stability and activity [122].…”
Section: Conclusion and Further Perspectivementioning
confidence: 99%